2014
DOI: 10.1049/iet-cds.2013.0211
|View full text |Cite
|
Sign up to set email alerts
|

Analysis study of sensitive volume and triggering criteria of single‐event burnout in super‐junction metal‐oxide semiconductor field‐effect transistors

Abstract: Power metal-oxide semiconductor field effect transistors (MOSFETs) are more and more used in atmospheric and space applications. Thus, it is essential to study the influence of the natural radiation environment on the electrical behaviour of vertical double-diffused metal-oxide semiconductor (VDMOS) and super-junction (SJ) MOSFETs. Two-dimensional numerical simulations are performed to define the sensitive volume and triggering criteria of single-event burnout (SEB) for VDMOS and SJ MOSFETs for different confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Thus, the generated currents lead to thermal runaway and burnout. Furthermore, the peak electric field is directly proportional to the impact ionisation coefficient, which is related to the SEB sensitivity [23,24]. Hence, the reduction of the peak electric field will improve the SEB performance [25].…”
Section: Seb Simulation Results and Discussionmentioning
confidence: 99%
“…Thus, the generated currents lead to thermal runaway and burnout. Furthermore, the peak electric field is directly proportional to the impact ionisation coefficient, which is related to the SEB sensitivity [23,24]. Hence, the reduction of the peak electric field will improve the SEB performance [25].…”
Section: Seb Simulation Results and Discussionmentioning
confidence: 99%
“…Ikeda et al [100] later showed experimentally that an SJ offered no improvement to SEB tolerance over a VDMOSFET. Further simulation and experimental studies on Si SJ MOSFETs showed there was no inherent advantage in SEE tolerance [101][102][103][104][105]. More recently, it has been demonstrated that SJ theory can be effective for SiC power MOSFETs [106], and the first SiC SJ MOSFET was demonstrated in [107] at the 2016 ESCRM.…”
Section: Baseline Superjunction Mosfet Seb Performancementioning
confidence: 99%